-22+2h=-9(6h-7)

Simple and best practice solution for -22+2h=-9(6h-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22+2h=-9(6h-7) equation:


Simplifying
-22 + 2h = -9(6h + -7)

Reorder the terms:
-22 + 2h = -9(-7 + 6h)
-22 + 2h = (-7 * -9 + 6h * -9)
-22 + 2h = (63 + -54h)

Solving
-22 + 2h = 63 + -54h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '54h' to each side of the equation.
-22 + 2h + 54h = 63 + -54h + 54h

Combine like terms: 2h + 54h = 56h
-22 + 56h = 63 + -54h + 54h

Combine like terms: -54h + 54h = 0
-22 + 56h = 63 + 0
-22 + 56h = 63

Add '22' to each side of the equation.
-22 + 22 + 56h = 63 + 22

Combine like terms: -22 + 22 = 0
0 + 56h = 63 + 22
56h = 63 + 22

Combine like terms: 63 + 22 = 85
56h = 85

Divide each side by '56'.
h = 1.517857143

Simplifying
h = 1.517857143

See similar equations:

| Y=4x^3+8 | | 4=2/9v | | -42x^6/27x^3 | | 7.5z+y+z=200 | | 0=-2x^4+2x^3+5x^2+18 | | 18.5=-3(2.5s+6) | | (4x+9)+(7x-13)+(2x-2)= | | -1.5a+12=12 | | 3w^4+60w^2-63=0 | | 7-(t+5)=6t+5 | | 9=-7m+7 | | 2/3x=6(1/5) | | 3(4x-3y)-(9x+2y-5)= | | 3/4/y=1/3 | | -8(2n-7)=20 | | 5c-8d-3c+4d= | | 3(r-4)+2r=-19+6r | | W^2-14w-15=0 | | -2x=-x^2+24 | | 2*x+1*x+1=14 | | x=-n-2 | | 26.5=-4.5c+8.5c | | 90-x+x=180 | | i/.16=.7 | | (1.5-x)(2-x)-2=0 | | 2x^4-4x^2-70=0 | | 46+-1+8x=12x+2 | | 3/10-1/5= | | 18=3x+1 | | 5a+3b-a-5b= | | x^4-3.5x^2+1=0 | | -3.8(2.7x-5.5)-8.4= |

Equations solver categories